The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.tranon.2020.100915
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AR-V7 downstream genes commonly targeted by AR/AR-V7 and specifically targeted by AR-V7 in castration resistant prostate cancer

Abstract: Highlights The entire landscape of AR-V7 target regions/genes in CRPC cells was investigated. We identified 78 AR-V7 target genes, targeted specifically by AR-V7 e.g. SLC3A2 , or commonly by AR and AR-V7 e.g. NUP210 . SLC3A2 and NUP210 were markedly upregulated in clinical CRPC tissues, leading to increased proliferation in CRPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 42 publications
0
42
0
Order By: Relevance
“…The studies seeking to elucidate variant action have yielded conflicting results. There is good agreement that AR-V7 and other variants can regulate many of the same genes, but there is a substantial debate about whether AR-V7 and other variants also regulate a substantial set of unique targets or have minimal or no unique activities [16][17][18][19][20]25,26,39 . Similarly, some investigators have identified unique AR-V7 chromatin binding sites, while others have described these as artifacts/unreliable 16,17,19,40 .…”
Section: Discussionmentioning
confidence: 99%
“…The studies seeking to elucidate variant action have yielded conflicting results. There is good agreement that AR-V7 and other variants can regulate many of the same genes, but there is a substantial debate about whether AR-V7 and other variants also regulate a substantial set of unique targets or have minimal or no unique activities [16][17][18][19][20]25,26,39 . Similarly, some investigators have identified unique AR-V7 chromatin binding sites, while others have described these as artifacts/unreliable 16,17,19,40 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recently identified 4F2hc as one of the main target genes for AR-V7. Upregulation of 4F2hc through AR-V7 contributes to the progression of CRPC 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of 4F2hc through AR-V7 contributes to the progression of CRPC. 23 Based on the above-described ndings, it may be reasonable to expect that 4F2hc is a promising prognostic biomarker, as well as a molecular target, in PC. In this study, the oncogenic function of 4F2hc in PC and its relationship with the clinical outcome of PC patients was studied.…”
Section: Introductionmentioning
confidence: 93%